In and out of English : for better, for worse? - Anderman, Gunilla M.; Rogers, Margaret, 1949 May 27- (Translating Europe., 2005)
In and out of English: For Better, For Worse? is concerned with the impact of English as the lingua franca of today's world, in particular its relationship with the languages of Europe. Within this framework a number of themes are explored, including linguistic imperialism, change as the result of language contact, the concept of the English native speaker, and the increasing need in an enlarged Europe for translation into as well as out of English.